STRATEGY FOR DEVELOPING INDONESIAN PEPPER EXPORT BASED ON TRADE PERFORMANCE INDEX AND ANALYTIC HIERARCHY PROCESS - Bedy Sudjarmoko; Agus Wahyudi; Ermiati Ermiati; Abdul Muis Hasibuan (Pusat Penelitian dan Pengembangan Perkebunan, 2015)
Production and export of Indonesian pepper in the world market has declined because of low in productivity, quality and product diversification, inefficient marketing chain and lack of technology transfer to farmers level. The study was conducted to identify and analyze export problems in pepper, and to formulate strategies and policies for pepper export development. This study used primary and secondary data. Data were analyzed with Trade Performance Index and Analytic Hierarchy Process. The results showed that the problems in Indonesian pepper export were low competitiveness and productivity, poor infrastructure, inappropriate institutional farmers and traders, high interest rates and improper policy implementation. The recommended grand strategies for pepper export development were resources optimization, infrastructure and institutional development, financing schemes, and strengthening policy implementation.